The relationship between transformational leadership and work engagement: Moderated mediation roles of psychological ownership and belief in just world - Fullchis Nurtjahjani; Ridolof Wenand Batilmurik; Ayu Fury Puspita; Jappy Parlindungan Fanggidae (Organization Management Journal (OMJ), 2022)
Purpose - This study aims to investigate the mediating and moderating effects of psychological ownership and belief in just world in the relationship between transformational leadership and work engagement. Design/methodology/approach - The data were collected from 183 lecturers who teach in an Indonesian university. The questionnaires covered transformational leadership, psychological ownership, belief in just world and work engagement. The collected data were examined with structural equation model analysis. Findings - The results demonstrated a significant moderated mediation index, which indicated that the relationship between transformational leadership and work engagement is mediated by psychological ownership and is moderated by belief in just world. Practical implications - To achieve higher work engagement, organizations should increase employees' feelings of ownership and boost just world belief. Originality/value - The present study offers new insight on how personality trait plays a moderating role in the relationship between transformational leadership and work engagement.
Keywords: 650; Public sector; Transformational leadership; Work engagement; Psychological ownership; Belief in just world